Social Media Influence on Consumer Behavior: The Role of E-WOM in Gfshop Online Purchases - Canra Krisna Jaya; Rosidi; Nisya Achdara (International Journal of Religious and Interdisciplinary Studies, 2024)
The increasingly tight development of the business world encourages business people to keep up with technological developments to compete with competitors. The emergence of marketplaces and the high number of marketplace users in Indonesia are opportunities to market and attract consumers' attention through communication strategies in sales. This study aims to determine the level of electronic word of mouth (E-WoM) communication, the level of purchase decisions of Gfshop followers, and the influence of E-WoM communication on purchase decisions in Gfshop online stores. This study uses a survey method with a simple regression technique. Data collection used a questionnaire in the form of a google form given to 100 respondents who followed the Gfshop account using an accidental sampling technique. Data processing and analysis using SPSS Statistics 22 software. The study results show that the E-WoM communication level of Gfshop followers is in the very high category (66%), and the purchase decision rate of Gfshop followers is also very high (52%). In addition, E-WoM communication influenced purchase decisions in the Gfshop online store, with a regression coefficient of 1.243 and a t-value of 8.052.